RETRACTED: Assessment of the effectiveness of the physical education process in preschool educational organizations - Qo’ldoshev Rustambek; Jumayeva Habiba; Husenova Aziza; Xaitov Lazizbek; Gudzina Victoria; Sanoyev G‘aybullo (E3S Web of Conferences, 2024)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001